Reseñas - Jesús Pérez García; Asunción Sainz; Nathalie Zimmermann; Fernando Magallanes; Dolors Sabaté; Juan-Fadrique Fernández; Olga Hinojosa; Rosa Marta Gómez Pato; Ángeles García Calderón; Eva Parra-Membrives (Futhark. Revista de Investigación y Cultura, 2021)
En este apartado se publican reseñas de trabajos científicos